The role of teacher educators and university supervisors to help student teachers reflect: from monological reflection toward dialogical conversation. Issue 2 (3rd March 2020) - Mau, Sue Tinsley; Harkness, Shelly Sheats
ABSTRACT: Within the study reported here, our broad aim was to think deeply about how to support student teachers as they assessed their students' mathematical understanding. Our experiences, as teacher educators, have been that although student teachers may recognize emerging student mathematical understanding, they are frequently unclear about how to use formative assessment for teaching decisions. Yet, increasingly, standards for teachers require them to focus on assessment. We analyzed data from one secondary mathematics student teacher, Kevin, in the form of video and transcripts of a teaching episode and his reflection which focused on his assessment of student learning. Salient issues emerged. Kevin emphasized classroom management and superficially assessed student understanding without evidence. Although time constraints pervade our profession, watching video with and posing questions that help student teachers identify the evidence of their students' mathematical understanding is critical. We conclude that teacher educators and university supervisors need to take a dialogical conversation approach to reflection because reflection must happen with others, not in isolation. We consider other implications for our own work with student teachers to help them grapple with the complexities of assessing student learning.